The Double-Edged Sword of ICT: Balancing Efficiency and Wellbeing in Nigeria’s Public Workforce - Bello, Mohammed Lawan; Isiaka, Sulu Babaita; Isiaka, Sulu Babaita; Akintola, Muslim Akinbola; Ameen, Abdullateef; Amosa, Jimoh Rafiu; Isiaka, Sulu Babaita; Adeoye, Tolulope Oluwaseun; AbdulKareem, Abdulrazaq Kayode (Advances in Humanities and Contemporary Studies, 2025)
This study examines the impact of Information and Communication Technology (ICT) adoption on employee wellbeing in the Nigerian public sector, focusing on the Kwara State Ministry of Water Resources. ICT has transformed workplace dynamics by improving efficiency, communication, and job satisfaction. However, its integration also presents challenges, including technostress, extended work hours, and blurred work-life boundaries. Using the Job Demands-Resources (JD-R) framework, Conservation of Resources (COR) theory, and Social Information Processing (SIP) theory, the study explores ICT’s dual role as both a job resource and a job demand. A quantitative research design was employed, with data collected through structured questionnaires from 136 employees. Findings indicate that ICT adoption significantly enhances job satisfaction and work-life balance while reducing stress through task automation. The study underscores the need for structured ICT policies, digital training programs, and workload management strategies to optimize ICT benefits while mitigating negative effects. Policymakers must prioritize digital infrastructure improvements and employee support mechanisms to foster a healthy work environment. Future research should explore long-term ICT effects on employee wellbeing and leadership roles in digital transformation.